Associations between gut microbiota and sarcopenia or its defining parameters in older adults: A systematic review - Laurence Lapauw; Aurélie Rutten; Jolan Dupont; Nadjia Amini; Laura Vercauteren; Muriel Derrien; Jeroen Raes; Evelien Gielen (Journal of Cachexia, Sarcopenia and Muscle)
Abstract Altered gut microbiota (GM) potentially contribute to development or worsening of sarcopenia through a gut‐muscle axis. This systematic review aims to compare GM between persons with sarcopenia or low sarcopenia‐defining parameters (muscle mass, strength, and physical performance) to those with preserved muscle status, as well as to clarify possible associations between sarcopenia (‐defining parameters) and relative abundance (RA) of GM‐taxa or GM‐(α‐ or β) diversity indices, in order to clarify whether there is robust evidence of the existence of a GM signature for sarcopenia. This systematic review was conducted according to the PRISMA‐reporting guideline and pre‐registered on PROSPERO (CRD42021259597). PubMed, Web of Science, Embase, ClinicalTrials.gov, and Cochrane library were searched until 20 July 2023. Included studies reported on GM and sarcopenia or its defining parameters. Observational studies were included with populations of mean age ≥50 years. Thirty‐two studies totalling 10 781 persons (58.56% ♀) were included. Thirteen studies defined sarcopenia as a construct. Nineteen studies reported at least one sarcopenia‐defining parameter (muscle mass, strength or physical performance). Studies found different GM‐taxa at multiple levels to be significantly associated with sarcopenia (n = 4/6), muscle mass (n = 13/14), strength (n = 7/9), and physical performance (n = 3/3); however, directions of associations were heterogeneous and also conflicting for specific GM‐taxa. Regarding β‐diversity, studies found GM of persons with sarcopenia, low muscle mass, or low strength to cluster differently compared with persons with preserved muscle status. α‐diversity was low in persons with sarcopenia or low muscle mass as compared with those with preserved muscle status, indicating low richness and diversity. In line with this, α‐diversity was significantly and positively associated with muscle mass (n = 3/4) and muscle strength (n = 2/3). All reported results were significant (P < 0.05). Persons with sarcopenia and low muscle parameters have less rich and diverse GM and can be separated from persons with preserved muscle mass and function based on GM‐composition. Sarcopenia and low muscle parameters are also associated with different GM‐taxa at multiple levels, but results were heterogeneous and no causal conclusions could be made due to the cross‐sectional design of the studies. This emphasizes the need for uniformly designed cross‐sectional and longitudinal trials with appropriate GM confounder control in large samples of persons with sarcopenia and clearly defined core outcome sets in order to further explore changes in GM‐taxa and to determine a sarcopenia‐specific GM‐signature.